Digital forensics: defining an education agenda - Nance, K.; Armstrong, Helen; Armstrong, Colin (IEEE Computer Society, 2010)
While many fields have well-defined education agendas, this is not the case for digital forensics. A unique characteristic of the evolution of digital forensics is that it has been largely driven by practitioners in the field. As a result, the majority of the educational experiences have been developed in response to identified weaknesses in the system or to train individuals on the use of a specific tool or technique, rather than as a result of educational needs assessments based on an accepted common body of knowledge. In June, 2008 a group of digital forensics researchers, educators and practitioners met as a working group at the colloquium for Information Systems Security Education (CISSE 2008) to brainstorm ideas for the development of a research, education, and outreach agenda for Digital Forensics. This paper presents the research in education needs that the group identified associated with the development of a digital forensics education agenda.